Tiến trình lịch sử trang phục và ứng dụng vào giảng dạy chuyên ngành tạo dáng và trang trí trang phục - Nguyễn, Thị Hoàn (Bộ Giáo dục và Đào tạo, 2013)
The object of this study is the history of custume in the world and Vietnam. That's a material to reference and study for the fashion professional students in their study and independent designs'.